Gambler's Fallacy as Behavioural Bias Of Young Investor - Dian Wijayanti; Tarsisius Renald Suganda; Feni Sufuiana Thewelis (Journal of Business and Behavioural Entrepreneurship, 2019)
This research aims to identify the behavioural bias of Gambler's Fallacy of young investors in Malang. This research was done by doing a survey method i.e. doing the dissemination of questionnaires to young investors in Malang. The number of samples gained from questionnaires were 108 respondents. questionnaires were assessed using Likert scale and analysed by using non-parametric test: Chi Square Test and Wilcoxon Signed-Rank Test to answer the hypothesis and research questions. The results showed that behavioural bias of Gambler’s Fallacy on young investors in Malang when they trade in uptrend and downtrend stock market with an equal probability. Based on the results, this research concluded that in making trading decisions, young investors in Malang are still very influenced by psychological factors and tend to follow their personal intuition. This shows that weak-form efficiency is inefficient.